Analysis of Students Creative Thinking Ability in Environmental Problem Solving - Meitiyani Meitiyani; Mega Elvianasti; Maesaroh Maesaroh; Irdalisa Irdalisa; Gufron Amirullah (AL-ISHLAH: Jurnal Pendidikan, 2022)
21st century is a period that requires the transformation of life including education in it. Changes that occur include increased interaction between individuals globally, the flood of open information, computing technology that reaches all types of work that can be done anywhere and anytime and the occurrence of cultural integration across borders and even countries. This situation requires individuals to have the resilience to adapt and survive in this century. The quality of teachers in education plays an important role in building various skills of students to face life's demands. Creative thinking skills are one of the competencies needed in this century. Fostering creativity in learning activities is very important to strengthen student resilience in the future. This study aims to provide an overview of students' creative thinking skills on environmental problems. This research uses quantitative descriptive methods. This article begins with the results of an assessment of the ability to think creatively in early semester students in the Biology Education study program major of Prof. Dr. Hamka University then analyze the factors that affect critical thinking skills through a questionnaire instrument to describe learning activities that build creative thinking skills both from the internal and external aspect.